2006
DOI: 10.1057/palgrave.jibs.8400230
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and leadership predictors of corporate social responsibility values of top management: a GLOBE study of 15 countries

Abstract: This paper examines cultural and leadership variables associated with corporate social responsibility values that managers apply to their decision-making. In this longitudinal study, we analyze data from 561 firms located in 15 countries on five continents to illustrate how the cultural dimensions of institutional collectivism and power distance predict social responsibility values on the part of top management team members. CEO visionary leadership and integrity were also uniquely predictive of such values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
486
1
18

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 605 publications
(547 citation statements)
references
References 46 publications
27
486
1
18
Order By: Relevance
“…Finally, this research contributes to extend knowledge about the impact of CSR on company performance beyond the US-EU, in the context of an emerging economy with a diverse socioeconomic and cultural context, an initiative that has been called for in the literature (e.g., Lau, 2011;Waldman et al, 2006). One can thus conclude that companies traded in the Brazilian stock market that invested on pension plans heaped strong and enduring benefits in the short, medium and long terms; those that invested on employee formal education heaped benefits as soon as the investments were made and in the medium term; and those that made stronger investments in healthcare and profit sharing heaped financial gains in the long term, within up to two years after such investments had been made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this research contributes to extend knowledge about the impact of CSR on company performance beyond the US-EU, in the context of an emerging economy with a diverse socioeconomic and cultural context, an initiative that has been called for in the literature (e.g., Lau, 2011;Waldman et al, 2006). One can thus conclude that companies traded in the Brazilian stock market that invested on pension plans heaped strong and enduring benefits in the short, medium and long terms; those that invested on employee formal education heaped benefits as soon as the investments were made and in the medium term; and those that made stronger investments in healthcare and profit sharing heaped financial gains in the long term, within up to two years after such investments had been made.…”
Section: Discussionmentioning
confidence: 99%
“…Managerial attitudes towards CSR and level of company engagement in CSR activities vary by country. Waldman et al (2006) have observed that managers in countries with high institutional collectivism and with low power distance traits, that is cultural values that focus on addressing longterm concerns and lessening inequity respectively, are more likely to show behaviors positively associated with CSR. Since Brazil is a country where institutional collectivism is average to low, and power distance is high (House, Hanges, Javidan, Dorfman, & Gupta, 2004), it should come as no surprise that CSR issues in the Brazilian business environment are still not as widespread as compared to other countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature refers to concepts such as ‗smart' [18] and ‗responsive' [20] regulation, involving a mix of regulatory and non-regulatory instruments. ‗Self-regulatory' mechanisms for sustainability have permeated corporate behavior, with an abundance of literature on corporations moving ‗beyond compliance' using environmental management practices, such as corporate social responsibility, triple bottom line reporting, and corporate citizenship initiatives such as the UN Global Compact and the EU's Eco-Management Audit Scheme (EMAS) [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. With the ISO 26000 guidelines (non-certifiable) on social responsibility for organizations to be released in 2010, voluntary mechanisms have gained credibility as a means to encourage sustainable corporate behavior beyond compliance.…”
Section: The Behavioral Underpinnings Of Regulationmentioning
confidence: 99%
“…Because corporations and their leaders are embedded in different national systems, they will embrace different societal values related to CSR (Schneider et al 2014;Waldman et al 2006) and experience divergent degrees of internal and external pressures to engage in CSR (Aguilera and Jackson 2010;Doh and Guay 2006;Matten and Crane 2005). For instance, Martin et al (2009), comparing business ethics between managers from Germany and the US, concluded that orientations and approaches to responsible leadership differ.…”
Section: Asian and Western Orientations To Responsible Leadership: Inmentioning
confidence: 99%